Do Interpersonal Conflict, Aggression and Bullying at the Workplace Overlap? A Latent Class Modeling Approach - Notelaers, Guy; Van der Heijden, Beatrice; Guenter, Hannes; Nielsen, Morten Birkeland; Einarsen, Ståle Valvetne (Frontiers in Psychology, 2018)
An unresolved issue in the occupational health literature that is of both theoretical and practical importance is whether interpersonal conflicts, aggression and bullying at work are distinct or overlapping phenomena for exposed workers. In this study, we addressed this question empirically by employing a Latent Class (LC) analysis using cross-industry data from 6,175 Belgian workers. We found that a two-factor solution with a conflict-aggression factor and a bullying factor had the best fit. Employees with low exposure to workplace conflicts-aggression and bullying perceived the phenomena as mostly overlapping. Reversely, employees who were exposed more frequently to the phenomena perceived them as more distinct - especially so for workplace bullying. Conflicts-aggression and bullying seem to be perceived as separate phenomena given their distinctive relationships with criterion variables in the domain of well-being and strain. These findings entail that a simple unifying approach or a single label for the three phenomena is not appropriate, at least from a measurement point of view and from the different perspectives of those exposed. Our results have important implications for the theoretical understanding of the concepts of interpersonal conflicts, aggression and bullying, and for practitioners who have to assist those involved with how to handle these problems and who have to develop legal as well as internal policies for the prevention and management of these issues at the workplace.